Perlindungan Hukum Kepada Konsumen Saat Berbelanja Online Menggunakan Sistem Pembayaran Cash on Delivery - Alid, Idul Hanzah; Ekaningsih, Lailasari; Tohari, Mohamad; Salsabila, Shafa' Diva; Oktavina, Sinta (Universitas Muhammadiyah Bima, 2025)
The rapid development of information technology has changed people's behavior in conducting transactions from conventional methods to electronic commerce (E-Commerce), where the Cash on Delivery (COD) payment system has become a popular option due to its convenience and efficiency. However, this buying and selling practice often poses legal risks and losses due to a lack of understanding of the rights and obligations of the parties involved. This study aims to analyze two main aspects: the legal basis governing the COD payment system in E-Commerce transactions and the forms of legal protection for consumers in such transactions. The research method employed is a normative juridical approach with an analytical and prescriptive focus, which involves reviewing literature and secondary data, as well as applicable legal norms, to provide arguments regarding emerging legal issues. The results of the study show that the legal basis for COD transactions in Indonesia is based on the Civil Code (KUHPer) concerning agreements, the Electronic Information and Transactions Law (UU ITE), and is specifically regulated in the Minister of Communication and Informatics Regulation Number 8 of 2025 concerning Commercial Postal Services, which provides a legal framework for on-site payment facilities. Legal protection for consumers is guaranteed through Law Number 8 of 1999 concerning Consumer Protection (UUPK), which regulates the right to comfort, security, and truthful information, as well as the obligation to act in good faith. In conclusion, existing regulations have established a robust legal framework to protect both consumers and business actors.